Editorial 11.1 - Lefoe, Geraldine (Journal of University Teaching and Learning Practice, 2014)
This issue is the first for Volume 11 of Journal of University Teaching and Learning (JUTLP) in 2014 and my final as Senior Editor as I move into retirement and finally have time to pursue my passion for photography. I am very proud of what has been achieved by JUTLP as an open access journal and have been supported by a wonderful editorial team in order to achieve this outcome. There have been 174 articles published in the 24 issues with 116000 full text downloads since 2008 when we were able to start collecting this data. There are many people involved in ensuring each issue is published and I’d like to thank all the authors, reviewers, editors and support staff who make this possible. I have valued your support, assistance and patience over the years and know you will continue to support this journal as a valuable contribution to teaching and learning in higher education. I congratulate the new Senior Editor, Associate Professor Romy Lawson who will lead the editorial team to take JUTLP in new directions. I wish them well and know they will enjoy the engagement with authors from around the world as much as I have.